Реабілітація мелодрами в українській екранній культурі - Журавльова, Т. (Студії мистецтвознавчі, 2008)
The development of the genre theory is a quite powerful direction of the modern art studies. The paper is devoted to the elucidation of the different aspects of forming and development of a melodrama as a genre in the entire cinema, and in the Ukrainian culture in particular.